Vessel Wall and Thrombogenesis - Endotoxin - McKay, Donald G (Thrombosis and Haemostasis, 1973)
The generalized Shwartzman reaction is a definitive disease process which is the result of two minor episodes of acute inflammation of the circulating blood. The identifying feature of the reaction is thrombosis of the micro circulation, specifically of glomerular capillary thrombosis which persists long enough to cause bilateral renal cortical necrosis. The reaction is the result of an interplay between leukocytes, platelets, complement, the contact system, the extrinsic prothrombin activator system, adrenal glucocorticoids, adrenal catecholamines, alpha - adrenergic receptor sites and the fibrinolytic enzyme system. The reaction occurs only when these systems are affected within narrow quantitative limits. It is a model of the effects of bacterial endotoxin on the blood-vascular system and has important implications for acute inflammatory episodes of the circulating blood induced by other inflammatory agents such as antigen-antibody complex and particulate matter.